Millennial Intention to Pay Zakat: The Effect of Religiosity and Attitudes - Purwadani, Eldiana; Ridlwan, Ahmad Ajib (UIN Sunan Kudus, 2022)
This study investigates religiosity's influence on paying zakat intention for millennials with attitude as a mediation variable. A Structural Equation Model (SEM) approach tests the measurement and structural model. The sampling technique is judgmental sampling to get 100 respondents through questionnaires distributed according to the characteristics of predetermined respondents. This study explains that religiosity and attitude positively and significantly affect paying zakat intention for millennials. In addition, this study also shows that attitude mediates the relationship between religiosity and paying zakat intention for millennials. This study provides a managerial implication for zakat institutions to have a better understanding that religiosity and attitude are essential to encourage Muslim millennials to pay zakat and the significant role of millennials in alleviating poverty in Indonesia.